1998
DOI: 10.1021/bi980854k
|View full text |Cite
|
Sign up to set email alerts
|

Truncation of Limonene Synthase Preprotein Provides a Fully Active ‘Pseudomature' Form of This Monoterpene Cyclase and Reveals the Function of the Amino-Terminal Arginine Pair

Abstract: The monoterpene cyclase limonene synthase transforms geranyl diphosphate to a monocyclic olefin and constitutes the simplest model for terpenoid cyclase catalysis. (-)-4S-Limonene synthase preprotein from spearmint bears a long plastidial targeting sequence. Difficulty expressing the full-length preprotein in Escherichia coli is encountered because of host codon usage, inclusion body formation, and the tight association of bacterial chaperones with the transit peptide. The purified preprotein is also kinetical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
216
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 249 publications
(225 citation statements)
references
References 49 publications
9
216
0
Order By: Relevance
“…Recombinant preparations were assayed with GGPP, ent-CPP, or syn-CPP as substrate and enzymatic activity detected using gas chromatography-mass spectrometry (GC-MS) analysis of organic extracts of the assays. Only the GST-OsDTS2 fusion protein exhibited appreciable amounts of activity, indicating the transit peptide (required for plastidial import in planta) hinders folding of the full-length preprotein in the absence of the stabilizing effect provided by the fused GST structure, as found in previous studies (Williams et al, 1998;Peters et al, 2000). Further, enzymatic turnover was only observed with syn-CPP, as no products were detected from reactions with GGPP or ent-CPP.…”
Section: Sequence Comparison Suggested a Role In Labdane-related Ditesupporting
confidence: 72%
“…Recombinant preparations were assayed with GGPP, ent-CPP, or syn-CPP as substrate and enzymatic activity detected using gas chromatography-mass spectrometry (GC-MS) analysis of organic extracts of the assays. Only the GST-OsDTS2 fusion protein exhibited appreciable amounts of activity, indicating the transit peptide (required for plastidial import in planta) hinders folding of the full-length preprotein in the absence of the stabilizing effect provided by the fused GST structure, as found in previous studies (Williams et al, 1998;Peters et al, 2000). Further, enzymatic turnover was only observed with syn-CPP, as no products were detected from reactions with GGPP or ent-CPP.…”
Section: Sequence Comparison Suggested a Role In Labdane-related Ditesupporting
confidence: 72%
“…As in other monoterpene synthases, a transit peptide sequence upstream to the absolutely conserved R 48 R 49 was found (Fig. 1) that may function in targeting the protein into plastids (Williams et al, 1998). Sequence analysis showed that the deduced protein was closest to monoterpene synthases from other angiosperms (Tpsb subfamily; Bohlmann et al, 1998;Fig.…”
Section: Cloning and Functional Analysis Of Qh6mentioning
confidence: 71%
“…PaTPS-Lin and PaTPS-Pin have very similar pIs at 5.71 and 5.79, respectively. cDNA clones of PaTPS-Lim, PaTPS-Myr, and PaTPS-Lin were full length and each included sequences for a putative N-terminal transit peptide of 62 to 64 amino acids upstream of a conserved RRX 8 W motif for import of mature proteins into plastids, characteristic of mono-TPS (Williams et al, 1998;Bohlmann et al, 1998b;Aubourg et al, 2002). PaTPS-Pin is slightly truncated, missing a starting Met.…”
Section: Results Cdna Cloning Of a Family Of Nine Tps Genes From Norwmentioning
confidence: 99%